Climate Change Adaptation Variations Influencing Market Participation and Performance among Youth Farmers - Gwebu, Mashoma Pusheletjo Nairobi; Tshikororo, Mpho; Khorombi, Takalani Isaac (Journal of Ecohumanism, 2025)
Climate change adaptation has been essential for food security. Agricultural market participation and performance depend on climate change adaptation, posing the need for farmers to adapt to climate change to meet the food demand. The current study sought to investigate how climate change adaptation variations influence youth farmers' market participation and performance. The study was conducted in the Thulamela local municipality of the Limpopo Province. The study used the purposive sampling method to select the 115 young farmers. The study used in-person interview sessions to administer structured questionnaires to the study participants. The study findings noted that climate change adaptation variation significantly influences market participation and performance among farmers. The study findings uncovered that farmers who did not adapt to climate change settle for an informal market and must keep revenue records due to inconsistency. While farmers who had adapted to climate change had secured market shares in the formal agricultural markets. The study recommends that future research be tailored towards the blended use of climate change adaptation strategies, which significantly enhance product qualities and improve market performance.